ANALISIS SIKAP KONSUMEN TERHADAP KUALITAS PERUMAHAN TYPE 36 - Abner Sitindaon; Mulyadi Raf; Ade Titi Nifita (DIGEST MARKETING, 2017)
This research aims to analyzing the costumers attitude to the housing of RSH with type 36, at Pesona Kenali Housing of Regional II National Housing Company. This research scope is limited at the research object, that’s: The costumers attitude who have bought and settled the housing of RSH with type 36 at Pesona Kenali Housing of Regional II National Housing Company, in the branch area of Jambi. This research takes the sample of 64 respondents by using the descriptive analysis purposively and this analysis, the written uses Fishbein model. This analysis with Fishbein model is used to know the customers attitude to one object based on the evaluation and the reaction to the result of average score of evaluation and convince, in giving the value rate of evaluation and convince, it uses the evaluation with likert scale. The research result show that customer attitude to the housing of RSH with type 36 is satisfactory enough. From the average value of all, it can be seen that the calculation of average score of the respondents attitude to the attributes in the housing of RSH type 36 is 333,42, including intervals that have good scores on the Likert scale (9-16), with the average score of attitude 12,727. Based on the research result above, this minithesis also recommends the National Housing Company to maintain and increase the housing quality especially the kitchen equipments which are regarded less satisfactory by the customers. The other facilities in the housing of RSH with 36 should be improved also, so that the housing can be occupied and aettled well or properly. Key word : Kualitas perumahan